2021
DOI: 10.32674/jis.v11i4.2541
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging, Intercultural and Academic Experiences among International Students at a University in Northern Ireland

Abstract: Higher education institutions have a strong interest in attracting international students, however, there is little research on international students' experience while studying in the UK and how this relates to their adjustment and belonging. This research was conducted with 16 international students at a HE institution in Northern Ireland, using qualitative interviews to examine academic and socio-cultural challenges they experience while studying and living in a country different from their own. Findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…SI into university departments is a big issue for doctoral education, resulting in students leaving their programmes and having lower academic achievements (Ellis 2001;Gardner 2007;Lovitts 2001). Previous studies showed that the level of SI could differ depending on the individual characteristics of doctoral students as well as characteristics of the educational environment (for instance, Antilla et al 2021;Cena et al 2021;Spencer-Oatey et al 2017). This study's main goal was to investigate differences in the SI of doctoral students at Russian universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SI into university departments is a big issue for doctoral education, resulting in students leaving their programmes and having lower academic achievements (Ellis 2001;Gardner 2007;Lovitts 2001). Previous studies showed that the level of SI could differ depending on the individual characteristics of doctoral students as well as characteristics of the educational environment (for instance, Antilla et al 2021;Cena et al 2021;Spencer-Oatey et al 2017). This study's main goal was to investigate differences in the SI of doctoral students at Russian universities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing SI between domestic and international students include Cena, Burns and Wilson (2021)…”
Section: Social Integration In Doctoral Studiesmentioning
confidence: 99%
“…see McCallum, 2022), travelling to a host country to experience a fully immersed education is still very much a goal of students around the world. Within the confines of this scenario, these students experience a vast array of challenges as they navigate their studies in a foreign culture and language (Cena, Burns and Wilson, 2021; Xiuwen and Razali, 2020). It is often the case that host universities and their staff are left to help support students in this navigation after they arrive in the host country/university.…”
Section: Added Value Of Artificial Intelligence Tools To Develop Tele...mentioning
confidence: 99%
“…doctors, police) towards international students/staff. Qualitative research with 16 international students in Northern Ireland (Cena et al, 2021) documents the multidimensional challenges faced by international students; pertaining to relationships and language. For example, students reported feeling left out of peer groups due to their accents, lack of belonging, and that they felt unwelcome.…”
Section: Conceptualising Internationalisation Through the Lens Of Eve...mentioning
confidence: 99%
“…лекара или полиције) о међународним студентима/факултетском особљу. Квалитативно истраживање на узорку од 16 међународних студената у Северној Ирској (Cena et al, 2021) документује вишедимензионалне изазове са којима се суочавају међународни студенти у погледу односа и језика. На пример, студенти су навели да се осећају изостављено из група својих колега због нагласка, неприпадања и осећаја да нису добро дошли.…”
Section: концептуализовање интернационализацијеunclassified